Práticas de microbiologia: relato de candida albicans em calopsita (nymphicus hollandicus) - Vinhas, Maria Carolina Cabral de Vasconcellos (Universidade Federal Rural do Semi-Árido, 2019)
In Brazil it is increasingly common to raise wild and exotic animals as companion animals, especially small mammals (rabbits, guinea pigs), birds (parakeets, cockatiels), reptiles (iguanas, jabutis) and fish ornamental (betta fish, neon cardial). Animals being bred in captivity are susceptible to various diseases, including those caused by microorganisms, which may have both primary and secondary origin. Thus, the greater the demand for care with specialized veterinarians and for effective diagnostic methods in identifying the various pathologies that can affect these animals. This study aimed to describe the activities carried out at the UFERSA Veterinary Microbiology Laboratory, from June 3 to July 31, highlighting the analysis of samples from the institution's wildlife clinic; present the case series of the received cases; and report a case of psittacine candidiasis of the species Nymphicus hollandicus. It is concluded that the microbiological diagnosis is an important aid for veterinarians, as there are still few data reported about the main etiological agents that affect wild and exotic animals, how they act in the animal's organism, and on the sensitivity or resistance of these agents to antimicrobials.
Relatório
Keywords: Levedura; Diagnóstico microbiológico; Psitacídeo; Yeast; Microbiological diagnosis; Psittacine; CIENCIAS AGRARIAS::MEDICINA VETERINARIA